Synthesis of a 5,6-Dihydropyran-2-one Derivative with Dual Anti-Cell-Migration and Anticancer Activity - Hamdy, Ahmed K.; Araki, Hiroshi; Tateishi, Hiroshi; Toma, Tsugumasa; Radwan, Mohamed O.; Biswas, Shashwata; Kuwata, Takeo; Matsushita, Shuzo; Fujita, Mikako; Niwa, Shin-ichiro; Otsuka, Masami (Synlett, 2025)
The 5,6-dihydropyran-2-one scaffold is found in several biologically active compounds. In this study, we synthesized a new derivative, named PY801. This compound (1 µM) was shown to suppress the migration of lung cancer cells. Furthermore, in cancer cell line panel experiments, PY801 showed cytotoxicity against several specific cell lines. The IC50 values of PY801 against colorectal cancer cells HCT116 and breast cancer cells MCF7 were determined to be 8.9 and 9.3 µM, respectively; these values are lower than those of the anticancer drug cisplatin. Compared with the IC50 against peripheral blood mononuclear cells (PBMC) from a healthy donor, the selectivity index was determined to be >7. This study showed PY801 might be a new lead compound for anti-cell-migration and anticancer drugs.
Keywords: dihydropyran-2-ones; anti-cell-migration activity; anticancer drugs